HIV/AIDS in Malaysia - Ismail, Rokiah (1998)
The population of Malaysia is 18.4 million, comprising 60% Bumiputra (or indigenous people which includes the aboriginal tribes, 10%, and 50% Malays), 28% Chinese, 8% Indians and 4% others. Eighty-five per cent of the population are aged 44 years and below. and 80.8% of the national workforce (defined as total employed individuals aged 15-64 years) are 15-44 years of age. With such a high percentage of the workforce being in the age group most affected by the HIV epidemic, a grave economic concern for the country is implied.